Peran Zakat Dalam Mengentas Kemiskinan - Afrah Afifah; M. Yarham (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article discusses the role of zakat in alleviating poverty. Where zakat is something that is obligatory for the Muslim community. In the Qur'an it is explained that zakat is a responsibility for the Muslim community to help each other. So it can be interpreted that zakat is a moral element. social, educational and economic. In terms of morals, zakat wards off the greed and stinginess of some Muslims who have a sufficient economy. In education, the obligation to give zakat can be taken from the feeling of wanting to give, donate and also give up some of the assets we own as a sign of our love for others. In social matters, namely zakat, the poor can play a role in their lives, carrying out their obligations to Allah SWT, helping with zakat and sadaqah that have been given from people who are capable. As is the case with zakat, underprivileged people feel like they are part of society, or not even outcasts and are looked down upon. In economic terms, zakat can play a role in preventing the accumulation of wealth in the hands of just one person, and also requires rich people to redistribute the wealth they have to rich and poor family groups. So, zakat functions as a potential source of funds in terms of alleviating poverty. Zakat can also be working capital for poor people to open up employment opportunities, so that this group can earn income and also be able to meet their daily living needs. Taken from the feeling of wanting to give, donate, and also give up some of one's wealth as a sign of compassion for fellow humans. In social matters, namely zakat, the poor can play a role in their lives, carrying out obligations to Allah SWT, helping with zakat and sadaqah that have been given from people who are capable.